A função socioambiental da propriedade industrial e o estímulo ao desenvolvimento sustentável: uma análise a partir da experiência obtida com o Programa Brasileiro de Patentes Verdes - Camargo, Michele Machado Segala (2018)
The present days have surfaced increasingly the environmental problem, forcing the adoption of a change of perspective, which it come influencing inclusive the scope of innovations. With effect, it has deserved featured the inventions that are proposed to develop any technique or process that contributes to the environment. Since it inly relational to technological innovations, Industrial Property has also been impacted by this change, being forced to assume new configurations, so that, besides constituting an important tool to leverage national development, it must also have a socio-environmental purpose. In this sense, one questioned to what extent the industrial property, through the Patent Office, can one present a fit mechanism to contribute to sustainable development. In order to obtain answers to this question, one started of the observed example with the Brazilian Green Patents Program, which was in place in Brazil until 2016. The methodology adopted is based on the following trinomial: Basic Theory or Approach, Procedure and Technique. As a basis theory, one opted for a systemic-complex approach, anchoring itself in the contributions provided by Fritjof Capra and Edgar Morin. As a method of use, one utilized of the bibliographic research and the documentary analysis, and as techniques of research, one elected drafting files and summaries.The research was divided into three chapters, each with three further subdivisions. The first of them, one dedicated to understanding the perspectives that Industrial Property has to offer for development, analyzing, from the plentiful dimensions of development, to the impacts that the international system of Intellectual Property exerts on national development. The second fetch a reflection about transposition of the socio-environmental function of traditional property to Industrial Property, permeating the notions introduced by the Green Economy. Finally, the last chapter discusses the possibilities of approaching development and sustainability through the patentability of green technologies, including an analysis about results obtained with the Brazilian Green Patents Program. By means of research work accomplished, one achieved to understood of that the patent institute can contribute, even indirectly, to a sustainable development, above all after the positive results observed with the Green Patents Program.